2005
DOI: 10.1152/ajpheart.01043.2004
|View full text |Cite
|
Sign up to set email alerts
|

Chemoreflex and metaboreflex control during static hypoxic exercise

Abstract: To investigate the effects of muscle metaboreceptor activation during hypoxic static exercise, we recorded muscle sympathetic nerve activity (MSNA), heart rate, blood pressure, ventilation, and blood lactate in 13 healthy subjects (22 +/- 2 yr) during 3 min of three randomized interventions: isocapnic hypoxia (10% O(2)) (chemoreflex activation), isometric handgrip exercise in normoxia (metaboreflex activation), and isometric handgrip exercise during isocapnic hypoxia (concomitant metaboreflex and chemoreflex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
5
40
1
1
Order By: Relevance
“…Metaboreflex activation selectively suppressed the peripheral sympathoinhibitotry effects of chemoreflex inhibition but left the cardiac inhibitory effects of hyperoxia unaffected. These results further extend our observation that MSNA and HR are regulated by different mechanisms during exercise (19).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Metaboreflex activation selectively suppressed the peripheral sympathoinhibitotry effects of chemoreflex inhibition but left the cardiac inhibitory effects of hyperoxia unaffected. These results further extend our observation that MSNA and HR are regulated by different mechanisms during exercise (19).…”
Section: Discussionsupporting
confidence: 90%
“…This is due to an increase in metaboreflex sensitivity by hyperoxia that overrules the sympathoinhibitory and BP lowering effects of chemoreflex inhibition. This occurs despite a reduced lactic acid production.handgrip; muscle sympathetic nerve activity; metaboreceptors; chemoreceptors MUSCLE METABORECEPTORS regulate sympathetic activation during exercise (19,25). This reflex is activated by metabolites released from exercising skeletal muscle.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators focused on coactivation of the muscle metaboreflex and hypoxic chemoreflex and reported no interaction and no specific effect on blood pressure response (39,14). By contrast, we found that blood pressure was higher during HCAϩMMA than HCA or MMA alone, but that the increase in MAP was smaller than the sum of the HCA and MMA responses.…”
Section: R45contrasting
confidence: 72%